110 Botulinum toxin for a refractory head tremor arising from cerebellar metastases. (23rd August 2021) - Blair, Christopher; Edwards, Leon; Cordato, Dennis
Abstract : Background: Tremor is an involuntary, rhythmic, oscillatory movement of a body part that can be a clinical manifestation of a range of underlying pathologies. 1 Of those tremor subtypes for which adequate management is often elusive, head tremor is among the most debilitating. Taking 'yes-yes', 'no-no', and mixed forms, available treatments for head tremor include medication, surgery, and botulinium toxin injections. 2 We report a case of severe head tremor arising from focal cerebellar metastases that showed a durable response to botulinium toxin treatments in a palliative setting, despite underlying disease progression. Case: A 60 year old lady was referred to our clinic with a 3 month history of 'no-no' head tremor. Originally diagnosed with ER - breast cancer in 2008, she underwent surgical resection but suffered a disease recurrence in 2017 when she presented with a solitary posterior fossa metastasis. This was resected and adjuvant radiotherapy was given, however in mid-2019 she developed first a left arm and then a coarse, persistent head tremor that severely limited her daily life. MRI brain revealed several new vermal and left cerebellar metastatic deposits. A combination of botulinium toxin injections to splenius capitis/sternomastoid and regular oral gabapentin effectively ameliorated her symptoms over three sessions. Discussion: Two open label studies and one RCT have shown that individualised botulinium toxin injections can be used to effectively treat essential head tremor 2, and we demonstrate here that such an approach may also be a useful in the management of head tremor due to rarer and more aggressive aetiologies. References: Louis ED. Diagnosis and management of tremor. Continuum (Minneap Minn) 2016 Aug;22(4 Movement Disorders):1143–58. Mittal SO, Lenka A, Jankovic J. Botulinum toxin for the treatment of tremor. Parkinsonism Relat Disord 2019 Jun;63 :31–41.